Prevención de la violencia: La voz de jóvenes adolescentes - Cerdas Agüero, Evelyn (2021)
This article explores the opinions and attitudes  of adolescents at school and out-ofschool in the community of Ciudad Colón  regarding their role in the prevention of violence. The research in which this articles is based, is a qualitative study and the research method is phenomenological, the techniques used were the in-depth interview, the biography and the Likert scale. The participant group was composed of schooled and non-schooled adolescents between 15and 17 years of age. The study shows that the participants consider that violence prevention implies results linked to greater personal safety, a decreasein direct violence, tranquility and is considered a way of influencing change in people so that there is less interpersonal violence. Opinions and attitudesare configured around assuming a personal role linked to prevention practices related to leisure and recreation, education, dialogue, solidarity, communication and information.